Growth hormone 1 gene (GH1) polymorphisms as possible markers of the production potential of beef cattle using the Brazilian Canchim breed as a model - Silveira, Luiz Guilherme G. [UNESP]; Furlan, Luiz R. [UNESP]; Curi, Rogerio Abdallah [UNESP]; Ferraz, André Luiz J. [UNESP]; Alencar, Maurício M. de; Regitano, Luciana C.A.; Martins, Cyntia Ludovico [UNESP]; Arrigoni, Mario de Beni [UNESP]; Suguisawa, Liliane [UNESP]; Silveira, Antonio Carlos [UNESP]; Oliveira, Henrique Nunes de [UNESP] (Sociedade Brasileira de Genética, 2008)
The growth hormone 1 gene (GH1) is a candidate gene for body weight and weight gain in cattle since it plays a fundamental role in growth regulation. We investigated the GH1 gene AluI and DdeI restriction enzyme polymorphisms, located 149 bp apart in the cattle genome, as possible markers of the production potential of Canchim crossbreed cattle, a 5/8 Charolais (Bos taurus) and 3/8 Nelore (Bos indicus) breed developed in Brazil, by evaluating the birth weight, weaning weight, yearling weight and plasma insulin-like growth factor-1 (IGF-1) concentration of 7 month to 10 months old Canchim calves (n = 204) of known genealogy and which had been genotyped for the AluI and DdeI markers. Our results showed significant effect (p < 0.05) between the homozygous DdeI+/DdeI+ polymorphism and the estimated breeding value for weaning weight (ESB-WW), while the AluI leucine homozygous (L/L) and leucine/valine (L/V) heterozygous polymorphisms showed no significant effect on the traits studied. The restriction sites of the two enzymes led to the formation of haplotypes which also exerted a significant effect (p < 0.05) on the ESB-WW, with the largest difference being 8.5 kg in favor of the homozygous L plus DdeI+/L plus DdeI+ genotype over the heterozygous L plus DdeI-/V plus DdeI+ genotype.
Keywords: beef cattle; polymorphism; growth hormone; candidate gene